Penstemon reidmoranii (Plantaginaceae), a new species from Baja California, Mexico - Zacarías-Correa, Ana Gabriela; Wolfe, Andrea D.; Martínez Salas, Esteban; Samain, Marie-Stéphanie (Phytotaxa, 2019)
Penstemon reidmoranii is described from the southern region of the state of Baja California, Mexico. This new species belongs to the subgenus Penstemon, section Peltanthera, subsection Peltanthera, and is distinguished primarily by its length, shape, margin and texture of the leaves. In addition, the staminode is covered in almost its full length by glandular hairs, while towards the apex it bears long white hairs of 6 mm long. Here, we describe and illustrate this new species. We also provide a distribution map and a comparison with Penstemon eximius, a morphologically similar taxon.